2011
DOI: 10.1107/s1600536811003898
|View full text |Cite
|
Sign up to set email alerts
|

Monocrotophos: dimethyl (E)-1-methyl-2-(methylcarbamoyl)ethenyl phosphate

Abstract: In the title compound, C7H14NO5P, the phosphate group displays rotational disorder of three O atoms with an occupancy ratio of 0.832 (6):0.167 (6). The dihedral angle between the acryl­amide group and PO2 plane of the phosphate group is 75.69 (7)°. In the crystal, inter­molecular N—H⋯O and C—H⋯O hydrogen bonds link the molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Conformational analysis (CA) studies are herein reported for simazine [ 9 ], monocrotophos [ 10 ], dimethoate [ 11 ], and acetamiprid [ 12 ] ( Table 3 ), as pesticides with known crystal structures, as well as for atrazine and carbofuran, as pesticides that exert the highest acute toxicity ( Table 4 ). To avoid redundancy, applied studies to the other pesticides are reported as Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conformational analysis (CA) studies are herein reported for simazine [ 9 ], monocrotophos [ 10 ], dimethoate [ 11 ], and acetamiprid [ 12 ] ( Table 3 ), as pesticides with known crystal structures, as well as for atrazine and carbofuran, as pesticides that exert the highest acute toxicity ( Table 4 ). To avoid redundancy, applied studies to the other pesticides are reported as Supplementary Material .…”
Section: Resultsmentioning
confidence: 99%
“…To avoid redundancy, applied studies to the other pesticides are reported as Supplementary Material . The crystal structures of simazine [ 9 ], monocrotophos [ 10 ], dimethoate [ 11 ], and acetamiprid [ 12 ] ( Table 3 , Tables S1–S3 ) were used as starting conformational geometries for the CA. For pesticides without experimental data ( Table 4 , Tables S1–S3 ), starting conformations were built from scratch and energy minimized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations